Lysophosphatidic Acid Improves Human Sperm Motility by Enhancing Glycolysis and Activating L-Type Calcium Channels - Li, Yinlam; Jin, Li; Li, Yanquan; Qian, Jianing; Wang, Zhengquan; Zheng, Xiaoguo; Xie, Chong; Zhang, Xuelian; Huang, Hefeng; Zhou, Yuchuan (Frontiers in Endocrinology, 2022)
Until now, the molecular mechanisms underlining sperm motility defect causing male infertility are still poorly understood. Safe and effective compounds or drugs that can improve sperm motility are also very limited. LPA is a naturally occurring phospholipid and a bioactive intermediate with multiple biological activities. It has been detected in various biological fluids such as serum, plasma, saliva, tears, blister fluids, hen egg white, and ascites from patients with ovarian cancer. LPA is also abundant in seminal plasma and follicular fluid. It enhances follicle stimulation, improves oocyte fertilization, and promotes early embryonic development and embryo implantation. However, the physiological role of LPA in the male reproductive system remains unknown. Here, our study showed that LPA significantly improved the motility parameters of human sperm hyperactivation in a dose-dependent manner. The LPA-induced elevation of sperm motility is dependent on bovine serum albumin (BSA) but independent of the classical BSA-induced sAC/cAMP/PKA signaling pathway. The enhancement of sperm motility by LPA was not blocked by CCCP, a respiratory inhibitor suppressed mitochondrial ATP production. Moreover, LPA improved the activity of triosephosphate isomerase in glycolysis. Meanwhile, LPA treatment significantly increased ATP and phosphoenolpyruvate levels and decreased ADP content in sperm during glycolysis. Notably, none of the LPA receptors identified are expressed in human sperm. Further investigations showed that LPA promoted sperm motility through L-type calcium channels. In summary, this study identified the involvement of LPA in the regulation for human sperm motility by enhancing glycolysis and activating L-type calcium channels. The present findings may shed new light on the understanding of causes of asthenozoospermia, and indicate that LPA may be used as a novel therapeutic agent to better sperm function and improved fertilizing capacity.